KRISIS ETIKA MAHASISWA DI ERA DIGITAL DALAM PERSPEKTIF HADIS: STUDI KASUS DI UNIVERSITAS ISLAM NEGERI SUMATERA UTARA MEDAN - Sri Aqilah Maulida; Ali Imran Sinaga; Rizki Nurbaiti Simanjuntak; Adinda Suhaibah; Ayu Wanda Ginting (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2026)
This research aims to examine the phenomenon of ethical crises among students in the digital age from the perspective of the hadiths of Prophet Muhammad (peace be upon him), with a focus on the etiquette of seeking knowledge within the State Islamic University of North Sumatra (UINSU) Medan. This research uses a qualitative approach with a descriptive-analytical research design. Data was obtained thru observation of students' academic behavior in face-to-face and online lectures, semi-structured interviews with students and lecturers, and documentation in the form of academic assignments and other supporting documents. This research is also supported by a literature review examining the hadiths of Prophet Muhammad (peace be upon him), classical Islamic texts such as Ta'līm al-Muta'allim by Az-Zarnuji and Iḥyā' 'Ulūm al-Dīn by al-Ghazali, as well as relevant contemporary scientific literature. The research findings indicate that UINSU Medan students are experiencing an academic ethics crisis characterized by a decline in the etiquette of seeking knowledge, a decrease in awareness of academic honesty, and an increasing dependence on digital technology, particularly the internet and artificial intelligence (AI). Forms of this ethical crisis include excessive reliance on AI without critical thinking, plagiarism and copy-pasting in academic assignments, and manipulation of research data due to time pressure and administrative demands. From the perspective of the hadiths of the Prophet Muhammad (peace be upon him) and Islamic scholarly traditions, this phenomenon reflects a weakening of the values of honesty (ṣidq), trustworthiness, diligence (mujāhadah), and sincerity of intention in seeking knowledge. Therefore, it is necessary to reinforce academic ethics based on the etiquette of seeking knowledge so that the use of digital technology aligns with the formation of students' character and intellectual integrity.